2020
DOI: 10.1001/jamanetworkopen.2020.14631
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Sex or Race With the Effect of Weight Loss on Physical Function

Abstract: This secondary analysis of 8 randomized clinical trials assesses whether stratification by sex and race is associated with meaningful differences in physical function response to weight loss among older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…In contrast, the risk estimates of functional disability were reduced in participants with regression of depression-obesity status from baseline to follow-up. The findings were in line with previously published literatures showing that treatment of depression or weight loss could restore functional ability [ 52 , 53 ]. Furthermore, a randomized controlled trial has demonstrated that compared to usual care, an integrated collaborative care intervention for individuals with comorbid depression and obesity could improve functional outcome measured by the Sheehan Disability Scale at 6 months, but not at 12 months [ 54 ].…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, the risk estimates of functional disability were reduced in participants with regression of depression-obesity status from baseline to follow-up. The findings were in line with previously published literatures showing that treatment of depression or weight loss could restore functional ability [ 52 , 53 ]. Furthermore, a randomized controlled trial has demonstrated that compared to usual care, an integrated collaborative care intervention for individuals with comorbid depression and obesity could improve functional outcome measured by the Sheehan Disability Scale at 6 months, but not at 12 months [ 54 ].…”
Section: Discussionsupporting
confidence: 92%
“…The effects of CL on adipocytes mirror the effects of exercise, especially regarding exercise-mediated increases in UCP1 [ 39 , 40 ]. Thus, it is interesting to note that there are also sex differences in exercise-mediated fat loss [ 41 , 42 ]. Such differences may be due to differences in ER signaling.…”
Section: Introductionmentioning
confidence: 99%
“…This is unsurprising as hip OA is more common in females than males [ 50 ]. Future clinical trials should consider stratifying by sex to balance the sexes across trial arms [ 51 ].…”
Section: Discussionmentioning
confidence: 99%